Privatization of State-Owned Enterprises Has Been Endorsed Globally Since 1990, but There are Still Many Companies in Government Hands. A Review of the Appropriate Corporate Governance Strategies for Managing These Companies and Those in Private Hands - Kwadade-Cudjoe, Francis (Advances in Social Sciences Research Journal, 2022)
The introduction of ‘information technology’ in the late 1950s brought in its wake increase in workflow efficiency which led to better performance of businesses to achieve organizational goals. Privatization of State-Own-Enterprises (SOEs) was championed by the formation of Organization for Economic Co-operation and Development (OECD) in the early 1960s to enable governments concentrate on their core mandate of managing their economies well. This has helped the OECD nations to perform better. However, there are still many companies in government hands, as these regimes still run, control and have oversight management of SOEs. The OECD, therefore, developed the Guidelines on Corporate Governance for SOEs to favour both the SOEs and privatized companies of nations in such a way that organizations would give better account of their stewardship to their citizenry. The guidelines introduced by the OECD are also to enhance the achievement of competitive advantage by organizations in the global economy of intense competition, especially during this technological age of business. For efficient management of all businesses, the OECD has also produced guidelines/principles for non-listed companies.